STRATEGI VALUE INVESTING: ANALISIS RETURN SAHAM UNDERVALUED BERDASARKAN RASIO KEUANGAN DI BURSA EFEK INDONESIA - Yoga Pradita, Rasyiid (ITB AAS Indonesia Surakarta, 2025)
This study is motivated by the misalignment between stock market prices and their intrinsic values, which creates opportunities for fundamental-based investment strategies, particularly value investing. The objective of this research is to examine the effect of fundamental indicators commonly used in value investing on stock returns in the Indonesia Stock Exchange (IDX). The research sample was determined through a screening process of all listed stocks on August 16–18, 2025, using closing prices as of August 15, 2025. The screening applied criteria including Price to Earnings Ratio (PER) below the market average (IDX PER = 13.55), Price to Book Value (PBV) < 1, positive Earnings Per Share (EPS), positive three-year growth of EPS (CAGR EPS), and Return on Equity (ROE) > 10%, resulting in 41 undervalued stocks as the final sample. Data were analyzed using multiple linear regression with SPSS version 25 after passing the classical assumption tests. The results indicate that individually PER, PBV, EPS, and ROE do not have a significant effect on stock returns. However, simultaneously, the four variables significantly influence stock returns with a significance value of 0.041 (<0.05). The coefficient of determination (R²) of 0.236 indicates that 23.6% of the variation in stock returns is explained by the model, while the remaining 76.4% is influenced by other factors outside the research model. These findings imply that value investing strategies in Indonesia require a multi-indicator approach and cannot rely solely on a single financial ratio.